Geographic Distribution of R&D Activity: How Does it Affect Innovation Quality? - Lahiri, Nandini (Academy of Management Journal, 2010)
I examine the impact of the geographic distribution of R&D activity on the quality of innovation. Through an analysis of patent data from 100 firms in the global semiconductor manufacturing industry, I find that the impact of geographic distribution of R&D on innovation quality takes an inverted-U shape and that firms are heterogeneous in the benefits derived from this geographic distribution. Results indicate that two characteristics—technological diversity of resources and intraorganizational linkages between R&D units—significantly influence firms' ability to derive benefits from increased geographic scope.